Strategi Pengembangan Usaha Keluarga Skala Mikro di Kota Palembang - Yulizar Kasih; Charisma Ayu Pramuditha (University of Merdeka Malang, 2021)
The purpose of this study is to determine the characteristics of the family business, internal strategic factors (strengths and weaknesses) and external (opportunities and threats) of the family business. This study analyzes various strategic alternatives that will be selected as a family business development strategy, then to determine the main strategies that can be implemented. ess by compiling a strategic business plan, implement the cooperation with external parties in the form of training and assistance related to product quality improvement, product innovation, preparation of financial rep This research is a descriptive study with 43 respondents as the research object selected by purposive and convenience sampling technique. The analyzed data uses descriptively by IFE-EFE matrix analysis and the SWOT matrix. The results from this study show that the family business was in a growth strategy position. Business development was carried out by increasing the scale of the busin orts, processing business licenses, online marketing (digital marketing), preparation of credit proposals, build the relationships with suppliers and maintain well-established relationships with customers.